Recent developments in monitoring of organophosphorus pesticides in food samples - Wondimu, Kokob Teshome; Geletu, Abiyot Kelecha; Kedir, Welela Meka (Journal of agriculture and food research, 2025)
Organophosphorus pesticides (OPPs) are extensively used in agriculture for pest control, but their chemical properties, toxicity, persistence, and potential environmental impact make them significant subjects of study. Monitoring OPP residues in food samples is crucial for ensuring food safety and regulatory compliance. Recent advancements in analytical methods have improved the detection, quantification, and identification of OPPs, enabling higher sensitivity, specificity, and throughput. This review highlights recent developments in sample preparation techniques providing a comprehensive overview of both traditional and modern approaches, including solid phase extraction and its miniaturized forms, QuEChER, and dispersive liquid liquid extraction, as well as advancements in chromatographic and spectroscopic methods, such as gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). It also examines the chemical properties of selected OPPs, detailing their modes of action, toxicity, and environmental persistence. Emerging sensor-based approaches, including electrochemical, optical, and molecular imprinted polymer-based sensors, are also discussed, offering rapid and on-site detection capabilities. This review concludes by emphasizing the current need for research and development to refine analytical methods, develop safer alternatives to OPPs, and strengthen regulatory frameworks for their use, ultimately aiming to protect consumers and the environment from the risks posed by these pesticides. [Display omitted] •Novel methods enhance detection of organophosphorus pesticides in food samples.•Advanced instruments improve sensitivity and accuracy in pesticide residue monitoring.•New extraction techniques increase efficiency in analyzing complex food matrices.•Multi-residue methods enable simultaneous detection of diverse pesticides in foods.•Emerging tools provide faster, cost-effective solutions for food safety monitoring.